Knowledge gaps in oncoplastic breast surgery. Issue 8 (August 2020) - Weber, Walter P; Morrow, Monica; Boniface, Jana de; Pusic, Andrea; Montagna, Giacomo; Kappos, Elisabeth A; Ritter, Mathilde; Haug, Martin; Kurzeder, Christian; Saccilotto, Ramon; Schulz, Alexandra; Benson, John; et al.
Abstract: The aims of the Oncoplastic Breast Consortium initiative were to identify important knowledge gaps in the field of oncoplastic breast-conserving surgery and nipple-sparing or skin-sparing mastectomy with immediate breast reconstruction, and to recommend appropriate research strategies to address these gaps. A total of 212 surgeons and 26 patient advocates from 55 countries prioritised the 15 most important knowledge gaps from a list of 38 in two electronic Delphi rounds. An interdisciplinary panel of the Oncoplastic Breast Consortium consisting of 63 stakeholders from 20 countries obtained consensus during an in-person meeting to select seven of these 15 knowledge gaps as research priorities. Three key recommendations emerged from the meeting. First, the effect of oncoplastic breast-conserving surgery on quality of life and the optimal type and timing of reconstruction after nipple-sparing or skin-sparing mastectomy with planned radiotherapy should be addressed by prospective cohort studies at an international level. Second, the role of adjunctive mesh and the positioning of implants during implant-based breast reconstruction should ideally be investigated by randomised controlled trials of pragmatic design. Finally, the BREAST-Q questionnaire is a suitable tool to assess primary outcomes in these studies, but other metrics to measure patient-reported outcomes should be systematically evaluated and quality indicators of surgical morbidity should be further assessed.